Moderating Effect of the Situation of Return or Relocation on the Well-Being and Psychosocial Trauma of Young Victims of the Armed Conflict in Colombia - Quintero-González, Sandra Milena; Madariaga-Orozco, Camilo Alberto; Millán-de Lange, Anthony Constant; Castellar-Jiménez, Diany Marcela; Palacio-Sañudo, Jorge Enrique (Frontiers in Psychology, 2020)
Colombia is the second country with the highest number of internally displaced persons. In the last 10 years, more than 400,000 young people carry, in their life experiences, the title of victims. The psychological and social circumstances that determine the lives of displaced young people in the world are not unknown. Fear, the poor resources for social adaptation available to them, and the possible reproduction of the cycle of violence, represent psychosocial risk factors in the young and displaced population. In this context, the Victims Law in Colombia stipulated various measures of repairment, including Relocation (the person or household victim of forced displacement decides to settle in some place, other than the one they were forced to leave) and Return (the person or the household victim of forced displacement decides to return to the place from which they were displaced, in order to settle indefinitely) provided the conditions of voluntariness, security, and dignity are present. A hypothesis that well-being will be better in the returnees was set, since they would strengthen the social support networks between neighbors and other victims in their old spaces of life. To test the hypothesis, the scales of Psychological Well-being, Social Well-being, the Satisfaction with Life Scale, and the Psychosocial Trauma Scale were applied to young returnees (n=129) and relocated (n=259) in Colombia. The Exploratory and Confirmatory Factor Analysis was performed to extract the general measure of well-being and psychosocial trauma followed by the comparison between the groups. Significance, power, and effect size indicators were obtained, and finally, the partial correlation between the groups was made in relation to psychosocial trauma and well-being. Results showed that returnees have greater well-being and clearer indicators (d=0.365, 1-β=0.996), with respect to that of relocated. In addition, the well-being of returnees has fewer trauma factors, who in turn are quasi-moderated by the situation of return or relocation.